Behavioral Responses to Uncertainty in Weight-Restored Anorexia Nervosa – Preliminary Results - Piccolo, Mayron; Milos, Gabriella Franca; Bluemel, Sena; Schumacher, Sonja; Mueller-Pfeiffer, Christoph; Fried, Michael; Ernst, Monique; Martin-Soelch, Chantal (Frontiers in Psychology, 2019)
Impaired decision-making under conditions of uncertainty seems to contribute to the expression and maintenance of anorexia nervosa (AN), but it is not clear whether this impairment is a disease state that would remit with treatment, or a persisting trait in patients with AN. To examine this question, a longitudinal study was conducted in 12 female inpatients with AN (age M = 22.2, SE = 1.36), before (Time-1) and after reaching a body mass index of >17.5 kg/m2 (Time-2). IU was assessed via a decision-making task, the wheel of fortune. Weight gain at Time-2 was accompanied with significant changes in uncertainty-related performance compared to Time-1 ([Time x Uncertainty], p < 0.05). At Time-1, reaction times varied in function of uncertainty, while at Time-2, uncertainty did not modulate reaction times. These findings support a change in decision-making under uncertainty with successful weight-rehabilitation in AN. While IU was present in underweight patients, it became non-significant after weight restoration.